PSIII-4 Evaluating Potential Interactive Effects of the IGF2 Intron3 g.3072a Substitution and Myostatin Loss-of-Function on Growth in Mice. (21st September 2022) - Chen, Xuenan; Dilger, Anna; Beever, Jonathan
Abstract: This study evaluated potential interactions between the Igf2 g.3072G >A mutation that increases IGF2 expression and Mstn loss-of-function (LOF) mutation on muscle and whole-body growth in mice. Mice (4 males, 4 females) from each of four genotypes were used including wild-type (WT, Mstn wt, Igf2 Gpat ), Mstn null (MN, Mstn -/-, Igf2 Gpat ), Igf2 intron3 g.3072A substitution (IGF2, Mstn wt, Igf2 Apat ), mice with both mutations (MI, Mstn -/-, Igf2 Apat ). Body weight (BW) was recorded weekly from 35-63d of age. At 63 ± 2d, mice were sacrificed and dissected. Muscle cell number, size and type was determined by immunohistochemistry from the tibialis anterior muscle. Data were analyzed as a 2x2x2 factorial with the main effects of Mstn status, Igf2 status, sex, and all interactions. At 49 and 56d of age, the Igf2 mutation increased body weight of mice by 8% (P< 0.05), while Mstn LOF increased BW by 13-20% (P< 0.05). At 63d of age, both main effects and interactions of Igf2 and Mstn were significant (P< 0.05). BW of MI mice was increased 34% compared with WT mice while BW of IGF2 was only numerically increased (4%, P>0.05) and weight of MN was increased (P< 0.05) 18%. This synergistic effect of Igf2 and Mstn mutations (P≤0.14) was also observed for increased carcass, gastrocnemius, heart, liver, and kidney weights. Mstn LOF consistently decreased (P≤0.02) fat pad weights. The effect of the Igf2 mutation on fat pad weight was mixed and did not interact with Mstn effects. Femur weight was unchanged by either mutation but was reduced (P< 0.01) in Mstn null mice as a percentage of BW. Mstn LOF promoted both muscle hyperplasia and hypertrophy and increased type IIB fiber percentage (P< 0.05), but Igf2 mutation only promoted muscle hypertrophy (P< 0.05). These data suggest the Igf2 G >A mutation promoted skeletal muscle and organ growth more effectively in the absence of Mstn in mice.